(untitled) - Said, Amina (Oxford, 2006)
Providing affordable access to scientific and technical research information is recognised worldwide as being an essential element in promoting national development. This case study, commissioned from the Higher Education Commission of Pakistan, documents how the setting up of a centralised national digital library can successfully meet that objective. It covers the content, training, marketing, finance, monitoring and evaluation and impact of the Digital Library, as well as plans for the future. The conclusion is that the Library is cost effective and that its impact on research has been positive.
Keywords: An toàn dữ liệu,Database security